Gross as well as microscopic anatomy and physiological functions of fetal placenta in Jaffrabadi buffaloes - Padodara, Ramesh Jamnadas; Singh, Vivek Kumar; Fefar, Dhaval Tribhovanbhai; Rameshbhai Bhadaniya, Amit; Ahlawat, Anshu Rampal; Savsani, Harish Hirjibhai; Mehta, Vijay Manoharbhai (Buffalo Bulletin, 2024)
The present study was conducted to know the gross morphology and histo-morphological structure of fetal placenta in Jaffrabadi buffaloes. Parameters like calf weight, placental weight, numbers, and size of cotyledons were observed in Jaffrabadi buffaloes and morphologically, fetal cotyledons were convex and non-pendunculated in Jaffrabadi buffaloes were found. Histological studies of small and large cotyledons showed extensive branching of secondary and tertiary villi that were longer, slender, and well developed in Jaffrabadi buffalo. A less developed basal lamina was seen in small cotyledon whereas developed basal lamina with numerous capillaries and connective tissue were observed in the large cotyledon. The diameter of trophoblast giant cells (TGC) in larger cotyledons were significantly (P<0.05) than the small cotyledons in expelled placenta at full term in Jaffrabadi buffaloes. A distinct distribution of carbohydrate and lipids in cotyledons were observed between large and small cotyledons as evident by acid mucopolysaccharides, neutral polysaccharides, and sudanophilic staining. Specific staining for calcium with Alizarin red stain showed that calcium is not present in a noticeable amount in small and large cotyledons. Isolation and culture of Jaffrabadi placental cells in M-199 medium with antibiotics and 2% FBS results in the efficient production of progesterone, estrogen, and testosterone. This study has shown that trophoblast cells are the actual sites for steroid hormone production. These cultured placental cells (1x106 cells/ ml) produce Progesterone, Estradiol-17β and Testosterone in the range of 1.72 to 2.12, 16.03 to 19.51 and 0.51 to 0.58 ng/ml, respectively in Jaffrabadi buffalo.